(untitled) (International Journal of Environmental Sciences, 2025)
This research examines soil contamination and microbial community composition over hydrological gradients in the industrially affected IDA Jeedimetla area, India. Stratified sampling from upper, middle, and lower gradient zones documented spatial variability in soil characteristics and pollutant dispersion. Physico-chemical tests indicated increased electrical conductivity and a neutral-to-alkaline pH in down-gradient areas, implying solute buildup. The Walkley-Black and ammonium acetate techniques revealed moderate levels of organic matter (1.6–2.2%) and cation exchange capacity (11–14 cmol(+)/kg). ICP-MS found elevated levels of bioavailable Zn (up to 160 mg/kg), Cu (110 mg/kg), and Pb (90 mg/kg) in the lower strata. GC-MS detected polycyclic aromatic hydrocarbons (e.g., benzo[a]pyrene, fluoranthene) and phenolic contaminants. Illumina 16S rRNA sequencing indicated reduced microbial alpha diversity and the predominance of stress-tolerant taxa (e.g., Pseudomonas, Sphingomonas) in contaminated areas. Diversity analyses validated unique community structures associated with pollution levels. These findings illustrate the synergistic effects of heavy metals and organic compounds on microbial ecology and endorse site-specific remediation solutions for industrially degraded soils.